1977
DOI: 10.1159/000241031
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Label in Maternal Plasma, Placenta, Fetal Plasma and Tissues after Injection of <sup>14</sup>C-Palmitate into the Circulation of 21- and 28-Day-Pregnant Rabbits

Abstract: Tissue and plasma samples were obtained from fetuses removed 1–20 min after injection of 14C-palmitate into the doe at day 21 or day 28 of gestation. Specific activity of maternal plasma free fatty acids (FFA) was higher, but that of fetal plasma FFA lower in 21- than 28-day-pregnant rabbits. In 21-day fetuses, total radioactivity in the liver never exceeded that in the placenta; in 28-day fetuses, the liver radioactivity exceeded that in the placenta after 3 min. Total radioactivity in the fetal br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1979
1979
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Plasma FFA can cross the placenta from mother to fetus in a number of animals, including rats (Hummel et al, 1975;Pascaud et al, 1977), guinea-pigs (Hershfleld andNemeth, 1969), rabbits (Van Duyne et al, 1962;Elphick et al, 1978Elphick et al, , 1979Hudson et al, 1977) and monkeys (Portman et al, 1969). There also is evidence that the human placenta is permeable to FFA (Rubaltelli et al, 1978;Hull and Elphick, 1979).…”
Section: Resultsmentioning
confidence: 99%
“…Plasma FFA can cross the placenta from mother to fetus in a number of animals, including rats (Hummel et al, 1975;Pascaud et al, 1977), guinea-pigs (Hershfleld andNemeth, 1969), rabbits (Van Duyne et al, 1962;Elphick et al, 1978Elphick et al, , 1979Hudson et al, 1977) and monkeys (Portman et al, 1969). There also is evidence that the human placenta is permeable to FFA (Rubaltelli et al, 1978;Hull and Elphick, 1979).…”
Section: Resultsmentioning
confidence: 99%
“…Elphick et al (1 1) demonstrated at 28 days gestational age, labeled palmitic acid administered to pregnant does appeared maximally in the fetal circulation within 3 min and had a half-life in the fetal circulation of 30-60 sec. The labeled fatty acids preferentially were incorporated into fetal phospholipids (15). Biezenski (5) has shown that esterified fatty acids and phospholipids do not cross HOURS Fig.…”
mentioning
confidence: 99%
“…Alors que la circulation et la captation par le foetus de mammifère des acides gras non essentiels tels que l'acide palmitique ont fait l'objet de recherches nombreuses (Hummel et al, 1974(Hummel et al, , 1975 Hudson et al, 1977) les recherches concernant les acides gras essentiels sont encore rares (Pascaud et al) …”
unclassified